Multifunctional Silica Nanoparticles for Covalent Immobilization of Highly Sensitive Proteins - Wang, Xu-Dong (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.